2012
DOI: 10.1089/ars.2012.4702
|View full text |Cite
|
Sign up to set email alerts
|

Redox Albuminomics: Oxidized Albumin in Human Diseases

Abstract: Application of specific redox proteomics techniques for the characterization of oxidized albumin forms in screening studies is required. A further challenge will be to analyze how these oxidative albumin modifications are related to real impact to the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 79 publications
2
135
0
Order By: Relevance
“…9) In addition, the distribution of HSA fractions may be used as a systemic redox marker because HSA is the most abundant protein in ECFs, and, thus, is responsible for the largest fraction of reactive sulfhydryl. 17) Mean value (74.7%) for HMA of young group (male, 21.6 years (n=8)) in this study was similar to that previously reported for young male subjects; 73.2% (22.1 years, n=20) 18) and 76.4% (29.1 years, n=10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9) In addition, the distribution of HSA fractions may be used as a systemic redox marker because HSA is the most abundant protein in ECFs, and, thus, is responsible for the largest fraction of reactive sulfhydryl. 17) Mean value (74.7%) for HMA of young group (male, 21.6 years (n=8)) in this study was similar to that previously reported for young male subjects; 73.2% (22.1 years, n=20) 18) and 76.4% (29.1 years, n=10).…”
Section: Discussionmentioning
confidence: 99%
“…4, a positive correlation was observed between carbonyl formation and thiol oxidation (r=0.840, p<0.001), however, the molecular mechanism responsible for oxidative modification markedly differed; for example, the specific target amino acid residues of proteins in carbonyl formation were Lys residues, 10) whereas that in thiol oxidation was the Cys residue. 9) Therefore, as in the case of thiol oxidative modification of isolated and recombinant HSA products for laboratory use, 11,12) significant amounts of carbonylated albumin in all medical-grade HSA products may be caused by long-time exposure to ROS during the manufacturing, isolation, and storage processes of plasma from human donors, even with special and careful treatments in the pharmaceutical industries. Anraku et al 25) also demonstrated that long-term (ca.10 h) exposure to a specific oxidative agent, 2,2′-azobis(2-amidino-propane) dihydrochloride (AAPH), resulted in a significant increase in the amount of carbonylated HSA obtained from human donors, even in the presence of albumin-specific stabilizers (N-Ac Trp and caprylate).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational changes in antibody targets presumably affect epitope binding, resulting in altered depletion efficiencies. Many groups have reported retention of nontargeted proteins, which may be due to homologous epitopes, nonspecific interactions with column matrices, or protein–protein interactions [13,26,31,35,36]. The closely controlled trypsin digestion protocol used here, employing single lots of reagents and enzyme and consistent incubation times, makes this step in and of itself unlikely to be a significant contributor to the variations observed.…”
Section: Discussionmentioning
confidence: 99%
“…HMA may be an important endogenous antioxidant within the body. Oxidized albumin forms have been shown to serve as early biomarkers for human diseases associated with oxidative stress [11,12] . Increased levels of oxidized albumin levels (high HNA level) have been reported in the serum of patients with end-stage renal disease [13,14] , though little is known about the relationship between the oxidized albumin content of the serum in patients on PD and the peritoneal membrane transport status.…”
mentioning
confidence: 99%